Application of the discrete-time structured singular value for DC-DC converters - Halton, M; Scharrer, M; Scanlan, T (IET Irish Signals and Systems Conference (ISSC 2008), 2008)
This paper considers the application of the discrete-time structured singular value to assess the robustness of systems subject to real parametric uncertainties. Since the associated uncertainty set is strictly real, the resulting μ bounds may be discontinuous irrespective of the fineness of the frequency sweep. It is therefore necessary to seek other more reliable methods of test. One such method detailed is a discrete robust stability state-space test that is not dependent on a frequency sweep. It is shown that this is a discrete skewed structured singular value problem. For illustration purposes, a robustness analysis using both a frequency sweep and state-space transformation is performed on a forward converter with a real parameter uncertainty. The results are detailed and critically assessed.